Work for Mother: The Ironies of Household Technology from the Open Hearth to the Microwave - Kealey, Linda (Labour / Le Travail, 1986)
This article reviews the book, "Work for Mother: The Ironies of Household Technology from the Open Hearth to the Microwave," by Ruth Schwartz Cowan.